Forms of aluminum in Brazilian acid soils with exceptionally high levels of KCl-extractable Al3+ Formas de alumínio em solos Ácidos Brasileiros com teores excepcionalmente altos de Al3+ extraível com KCl - Cunha G.O.M.* (2015)
© 2015, Revista Brasileira de Ciencia do Solo. All rights reserved.Exchangeable Al is normally quantified in the extract of 1.0 mol L-1 KCl, but Al does not always come solely from exchangeable forms of the element. The objective of this study was to quantify Al forms existing in acid soils in order to elucidate if all Al-KCl comes from exchangeable forms. Soils samples with different mineralogical compositions were collected from many regions of Brazil. The following Al extractants were evaluated: the traditional method (1.0 mol L-1 KCl) and some variations of it (potentiometric titration curves, method of successive extractions, and 1.0 mol L-1 KCl buffered at pH 5.0), 0.1 mol L-1 KCl, 0.01 mol L-1 CaCl2, 0.2 mol L-1 ammonium oxalate, 0.1 mol L-1 sodium pyrophosphate, and 0.5 mol L-1 CuCl2. Aluminum was quantified by titration, or by atomic absorption spectroscopy when pertinent. Samples from A and B horizons were used that were collected from five Brazilian states: Acre, Bahia, Pernambuco, Santa Catarina, and Rio Grande do Sul. Two additional soil profiles with lower contents of Al and essentially kaolinitic mineralogy were used as a reference of more weathered soils. Results showed that especially in acid soils with smectite, 1.0 mol L-1 KCl extracts other forms of Al in addition to the exchangeable form, which makes this solution inappropriate for estimating exchangeable Al for most soils studied. However, use of this solution in a more dilute form (0.1 mol L-1 KCl) had a smaller effect on the dissolution of these compounds and is a more reliable indicator of exchangeable Al levels. The other variations of this method (buffer pH 5, and potentiometric and successive extraction methods) were not suitable for determining this element because they extracted similar or even higher amounts when compared to the traditional method. The high contents of Al quantified by ammonium oxalate, copper chloride, and sodium pyrophosphate extractants showed the expressive participation of amorphous inorganic forms and low crystallinity, which contributed to overestimating the levels of Al in the soils studied.